2022
DOI: 10.3389/fneur.2022.934670
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal synergies and associated reactions post-hemiparetic stroke reflect muscle activation patterns of brainstem motor pathways

Abstract: Individuals with moderate-to-severe post-stroke hemiparesis cannot control proximal and distal joints of the arm independently because they are constrained to stereotypical movement patterns called flexion and extension synergies. Accumulating evidence indicates that these synergies emerge because of upregulation of diffusely projecting brainstem motor pathways following stroke-induced damage to corticofugal pathways. During our recent work on differences in synergy expression among proximal and distal joints,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 52 publications
1
13
1
Order By: Relevance
“…These hyperexcitable motoneurons are much more sensitive to afferent inputs which may lead to spasticity and even hypertonicity, where individuals are unable to derecruit and cease discharge of motoneurons. Furthermore, more excitable motoneurons also amplify the commands of weak and indirect motor pathways (e.g., reticulospinal) which is theorized to generate a loss of independent joint control (Dewald et al, 1995, Ellis et al, 2016, Li et al, 2019, McPherson et al, 2018a, McPherson et al, 2018c, McPherson and Dewald, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These hyperexcitable motoneurons are much more sensitive to afferent inputs which may lead to spasticity and even hypertonicity, where individuals are unable to derecruit and cease discharge of motoneurons. Furthermore, more excitable motoneurons also amplify the commands of weak and indirect motor pathways (e.g., reticulospinal) which is theorized to generate a loss of independent joint control (Dewald et al, 1995, Ellis et al, 2016, Li et al, 2019, McPherson et al, 2018a, McPherson et al, 2018c, McPherson and Dewald, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, more excitable motoneurons also amplify the commands of weak and indirect motor pathways (e.g., reticulospinal) which is theorized to generate a loss of independent joint control (Dewald et al, 1995, Ellis et al, 2016, Li et al, 2019, McPherson et al, 2018a, McPherson et al, 2018c, McPherson and Dewald, 2022.…”
Section: Implications: Neurological Impairment and Muscle Crampsmentioning
confidence: 99%
“…We also found that muscle individuation was poorer during FDI task performance than BIC performance; in other words, non-instructed muscles throughout the UE showed greater activity during controlled movement at the index finger than elbow. These results differ from other chronic stroke studies that found worse individuation with proximal movement (Zackowski et al ., 2004; McPherson & Dewald, 2022) or no segmental difference (Lang & Beebe, 2007). This disagreement may reflect differences in how non-instructed muscle activity was elicited.…”
Section: Discussionmentioning
confidence: 99%
“…Of the chronic stroke studies that compared motor behaviors between segments, most used subjective clinical scales or unmatched testing paradigms. This has led to conflicting results, with some investigators finding differences in particular segmental behaviors (Lang et al, 2006;Cho et al, 2012) (Zackowski et al, 2004;McPherson & Dewald, 2022) and others finding none (Mercier & Bourbonnais, 2004;Lang et al, 2006;Lang & Beebe, 2007). Collectively, these observations call into question whether segmental behavioral differences exist in the chronic phase or are an artifact of the testing instruments.…”
Section: Introductionmentioning
confidence: 99%
“…Synergy-driven elbow flexion is thought to arise from a greater reliance on the reticulospinal tracts (RST) post stroke, and their relatively diffuse projections to multiple motor pools (Dewald et al ., 1995; Owen et al ., 2017; Karbasforoushan et al ., 2019; McPherson & Dewald, 2022). In short, due to the diffuse projections of the RST, excitatory drive intended for motoneurons of the shoulder abductors produces an involuntary activation of elbow flexor motoneurons.…”
Section: Discussionmentioning
confidence: 99%